u+-5/6=-2/6

Simple and best practice solution for u+-5/6=-2/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for u+-5/6=-2/6 equation:



u+-5/6=-2/6
We move all terms to the left:
u+-5/6-(-2/6)=0
We add all the numbers together, and all the variables
u-5/6-(-2/6)=0
We get rid of parentheses
u-5/6+2/6=0
We multiply all the terms by the denominator
u*6-5+2=0
We add all the numbers together, and all the variables
u*6-3=0
Wy multiply elements
6u-3=0
We move all terms containing u to the left, all other terms to the right
6u=3
u=3/6
u=1/2

See similar equations:

| 2y+3y-y+5=y+23 | | 4x=53/5 | | (5x)+(x+6)=90 | | -8+7+4x=113 | | 6x+3x+25=2x+x+55 | | -7t+5=54 | | 6/7w=-36 | | 3x-8+5x-6+4x+2=180 | | -1/6z=7/12-1/12 | | 7q-15=76 | | 300x+50=298x+100 | | -1x+14=-9.8+x | | 5+9u=86 | | x+8/3=-7 | | 7(x-7)/2=12 | | 10x+20+30+5x=10x+13x+90 | | 5x+4+x=-56 | | u/4+37=43 | | x+3x+15=6x+3 | | 3x+20=43 | | 8x-10+10x-40+3x+20=180 | | 4=p/4-2 | | 12=6x-3x+9 | | 145+x=165 | | 3x+4x+35=200 | | z-76/4=4 | | H=4.9d | | Y=0/1x+2 | | 3x+2x-3+x+3=180 | | 3+7j=38 | | n+10=2n+3 | | H(t)=9t^2-24t+16 |

Equations solver categories